Parallel-ski device "twincarver" for differential learning in downhill skiing - Hurih, P.; Schöllhorn, W. I. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: For learning and improving alpine skiing technique versatile methods, tools and equipments are applied. A basic idea of the most of these learning aids is to offer some-thing similar to the intended target movement on different levels of observation, On a most abstract level gliding skills in general are considered as supportive for alpine skiing. A Problem with respect to the application of most popular snow sport equipment like Snow-board, Mono-ski, Telemark-ski or Sqwal towards transfer on alpine skiing technique are their different degrees of freedom, their different numbers and sides of gliding edges. Due to these differences the offered space of movement solution is assumed to have too little commonalities with alpine skiing technique. The aim of this project was to develop a snow sport tool that provides I) more phenomenological similarities with downhill skiing for enlarging an athletes future movement space of solutions, II) differences in the learning process for stabilizing the potential downhill skiing race behavior.